Peran Guru dalam Mengembangkan Pembelajaran IPAS Berbasis Kearifan Lokal untuk Meningkatkan Pemahaman Kontekstual Siswa Sekolah Dasar: The Role of Teachers in Developing Local Wisdom-Based Science Learning to Improve Elementary School Students' Contextual Understanding - Albinus Taem; Pitalis Mawardi Baging (ITScience (Information Technology and Science), 2026)
Science learning in elementary schools requires a contextual learning process so that students are able to understand concepts meaningfully and relevant to everyday life. Utilizing local wisdom is a strategic alternative because it can connect learning materials with students' socio-cultural environment. Conditions at SD Negeri 02 Sungai Melayu Rayak, Ketapang Regency, show the potential of the river environment, plantations, and local community life that can be utilized as learning resources. This study aims to describe and analyze the role of teachers in developing science learning based on local wisdom in improving students' contextual understanding. The study used a qualitative approach with a descriptive type. The research subjects consisted of teachers and students who were selected purposively. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of teachers is realized as learning designers, facilitators, cultural mediators, and evaluators. The implementation of learning is carried out by linking science material with local contexts such as river ecosystems, plantations, and community activities so that learning becomes more meaningful. Students' contextual understanding improved through their ability to connect concepts to everyday life, explain environmental phenomena, and demonstrate concern for environmental sustainability. Supporting factors included local environmental potential and active student involvement, while barriers included limited planning, teacher preparedness, and learning media. This study concluded that local wisdom-based science learning is effective in improving students' contextual understanding when supported by optimal teacher involvement, systematic learning management, and the use of the local environment as the primary learning resource.